2013
DOI: 10.1155/2013/806374
|View full text |Cite
|
Sign up to set email alerts
|

Growth of MoO3 Films by RF Magnetron Sputtering: Studies on the Structural, Optical, and Electrochromic Properties

Abstract: Molybdenum oxide (MoO3) films were deposited on glass and silicon substrates held at temperature 473 K by RF magnetron sputtering of molybdenum target at various oxygen partial pressures in the range 8×10-5–8×10-4 mbar. The deposited MoO3 films were characterized for their chemical composition, crystallographic structure, surface morphology, chemical binding configuration, and optical properties. The films formed at oxygen partial pressure of 4×10-4 mbar were nearly stoichiometric and nanocrystalline MoO3 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“… 40 A broad peak observed at ∼811 nm is due to the bridging vibration of Mo O and indicated that the existence of Mo 6+ oxidation state is related to the α-MoO 3 phase. 73 Two absorption peak located at ∼901 and 1002 cm −1 , associated with the stretching vibration of Mo O, which is the specification of terminal double bonds. This confirms the basic characterises of a layered structure of α-MoO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 A broad peak observed at ∼811 nm is due to the bridging vibration of Mo O and indicated that the existence of Mo 6+ oxidation state is related to the α-MoO 3 phase. 73 Two absorption peak located at ∼901 and 1002 cm −1 , associated with the stretching vibration of Mo O, which is the specification of terminal double bonds. This confirms the basic characterises of a layered structure of α-MoO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…71 The characteristics absorption peaks for a-MoO 3 phase of the sample S 1 and S 2 are located at $502, 648, 811, 901, 1002 cm À1 and $502, 512, 674, 811, 901, 1002 cm À1 , respectively. 11,24,40,55,[72][73][74] In addition, two absorption peaks of h-MoO 3 phase are appeared at $548 and 711 cm À1 for the sample S 1 . 67 The magnied area of the FTIR absorption spectra in wavenumber range, 400-1040 cm À1 corresponding to the samples: S 1 and S 2 are shown in the inset of Fig.…”
Section: Crystal Structure and Particle Size Analysismentioning
confidence: 93%
“…[103] The noise was decreased when compared with the previous sensor design. [30,53] It was difficult to miniaturize the fluxgate sensor because the noise would increase if the sensor size were decreased. Fluxgate sensors are tiny in size, which enables us to use them in micro/ nanoelectronics technologies.…”
Section: Advancements In Microtechnology Fluxgate Sensormentioning
confidence: 99%
“…In this way, the material will deposit on the wafer. [30] In EBL, however, a mask for the specified coil pattern will be designed. They have mainly utilised nanoscale size designs.…”
mentioning
confidence: 99%
“…Color centers (F-centers) can form via UV illumination, 11 thermal treatment and applying an electric field. 12 .…”
Section: Introductionmentioning
confidence: 99%